Early‐life exposure to sibling modifies the relationship between CD14 polymorphisms and allergic sensitization. Issue 3 (13th November 2018) - Lau, Melisa Y. Z.; Dharmage, Shyamali C.; Burgess, John A.; Win, Aung K.; Lowe, Adrian J.; Lodge, Caroline J.; Perret, Jennifer; Hui, Jennie; Thomas, Paul S.; Giles, Graham; Thompson, Bruce R.; Abramson, Michael J.; et al.
Summary: Background: Markers of microbial exposure are thought to be associated with risk of allergic sensitization; however, the associations are inconsistent and may be related to gene‐environment interactions. Objective: To examine the relationship between polymorphisms in the CD14 gene and allergic sensitization and whether sibling exposure, as a marker of microbial exposure, modified this relationship. Methods: We used data from the Tasmanian Longitudinal Health Study and the Melbourne Atopy Cohort Study. Two CD14 polymorphisms were genotyped. Allergic sensitization was defined by a positive response to a skin prick test. Sibling exposure was measured as cumulative exposure to siblings before age 6 months, 2 and 4 years. Logistic regression and multi‐level mixed‐effects logistic regression were used to examine the associations. Effect estimates across the cohorts were pooled using random‐effects meta‐analysis. Results: CD14 SNPs were not individually associated with allergic sensitization in either cohort. In TAHS, cumulative sibling exposure before age 6 months, 2 and 4 years was each associated with a reduced risk of allergic sensitization at age 45 years. A similar effect was observed in MACS. Meta‐analysis across the two cohorts showed consistent evidence of an interaction between cumulative sibling exposure before 6 months and the rs5744455‐SNP ( P  = 0.001) but not with the rs2569190‐SNP ( P  = 0.60). The pooled meta‐analysis showed that the odds of sensitization with increasing cumulative exposure to sibling before 6 months of age was 20.9% smaller in those with the rs5744455‐C‐allele than the T‐allele (OR = 0.83 vs 1.05, respectively). Conclusion and Clinical Relevance: Cumulative sibling exposure reduced the risk of sensitization from childhood to middle age in genetically susceptible individuals.